Fenton's reagent for the rapid and efficient isolation of microplastics from wastewater. Issue 2 (9th December 2016) - Tagg, A. S.; Harrison, J. P.; Ju-Nam, Y.; Sapp, M.; Bradley, E. L.; Sinclair, C. J.; Ojeda, J. J.
Abstract : Fenton's reagent is a very useful preparation method for the efficient and bias-free analysis of microplastics. The catalytic reaction did not affect microplastics chemistry or size, offering a simple, high-speed and low-cost method for processing microplastics present in wastewater or other complex media. Abstract : Fenton's reagent was used to isolate microplastics from organic-rich wastewater. The catalytic reaction did not affect microplastic chemistry or size, enabling its use as a pre-treatment method for focal plane array-based micro-FT-IR imaging. Compared with previously described microplastic treatment methods, Fenton's reagent offers a considerable reduction in sample preparation times.